PELATIHAN SISTEM INFORMASI SIMPAN PINJAM PADA KOPERASI WANITA MIFTAHUL JANNAH DI KABUPATEN TULUNGAGUNG - Maskur Maskur; Yosi Afandi; Nilawati Fiernaningsih; Pudji Herijanto; Yulis Nurul ‘Aini (Publisher UPT P2M Politeknik Negeri Malang, 2022)
Current technological developments require human resources to be able to follow the use of technology. One of the technological developments that is quite widely used is information systems. An information system is a system within an organization that meets the needs of daily transaction processing, supports operations, is managerial and strategic activities of an organization and provides certain outside parties with the necessary reports. Miftahul Jannah Women's Cooperative currently still uses a manual savings and loan system, so the possibility of data errors is still quite large and services to members take a relatively long time. This information system for women aims, among other things, to help facilitate cooperative officers and administrators in completing their duties to serve members easily and quickly, to improve services to members. The development of this cooperative information system uses the RAD (Rapid Application Development) method, the Lecture Method and the Training Method. The RAD method is used for the process of forming an information system, the RAD method is a system development that prioritizes the speed of development through the involvement of the user or users in the use of a series of systems so that the possibility of system errors can be minimized, the Lecture and Training Method is used to provide explanations to the cooperative management about how to operate system, thus human resources can be trained to be able to use the use of technology.